STRATEGI HUBUNGAN MASYARAKAT SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI ERA DIGITAL - Abdul Jabar Idharudin; Muwahidah Nurhasanah; Budi Heriyanto, Budi Heriyanto (As-Sulthan Journal of Education, 2025)
Effective communication between schools, parents, and the community is essential for improving the quality of education in the digital era. This study aims to analyze the public relations strategies implemented by SMP Ibnu Aqil in enhancing parental and community involvement, as well as their impact on student educational quality. The research method used is qualitative with a case study approach, which includes direct observation, in-depth interviews with public relations staff, curriculum managers, and the school principal, and documentation of public relations services data. The data analysis technique applied is triangulation to ensure the validity and reliability of the findings. The results show that SMP Ibnu Aqil successfully utilizes digital media, such as social media and websites, to convey information to the community, build its image, and strengthen two-way communication with parents. Parental involvement in school activities has increased, positively impacting student motivation and achievement. The implications of this research indicate that effective public relations strategies and the utilization of digital media can serve as a model for other schools in improving educational quality. This study recommends that schools in Indonesia continue developing programs that actively involve parents and the community, thereby creating a more supportive and collaborative learning environment.